Anion‐Coordination‐Assisted Assembly of Supramolecular Charge‐Transfer Complexes Based on Tris(urea) Ligands. Issue 6 (22nd January 2020) - Zhang, Dan; Hou, Le‐Kai; Zhang, Qiang; He, Jia‐Wei; Feng, Hong‐Jian; Würthner, Frank; Yang, Xiao‐Juan; Wu, Biao
Abstract: Charge‐transfer (CT) complexes, formed by noncovalent bonding between electron‐rich (donor, D) and electron‐deficient (acceptor, A) molecules (or moieties) have attracted considerable attention due to their fascinating structures and potential applications. Herein, we demonstrate that anion coordination is a promising strategy to promote CT complex formation between anion‐binding, electron‐rich tris(urea) donor ligands (D) and electron‐deficient viologen cation acceptors (A), which form co‐crystals featuring infinite ⋅⋅⋅DADA⋅⋅⋅ or discrete (circular DADA or three‐decker DAD) π‐stacking interactions. These CT complexes were studied by X‐ray diffraction, UV/Vis spectroscopy, electric conductivity measurements, charge displacement curve (CDC) calculations, and DFT computations. Abstract : Charge transfer (CT) complexes, formed by noncovalent bonding between electron‐rich and ‐deficient molecules, have attracted much attention for a variety of applications. It was shown that anion coordination can provide an alternative strategy to promote the formation of π stacks with CT interactions between tris(urea) ligands and viologen cations, through infinite ⋅⋅⋅DADA⋅⋅⋅ or finite DAD π‐stacking interactions.